Graft-versus-Host Disease after Living-Unrelated Kidney Transplantation - N. Zacharias; M. H. Gallichio; D. J. Conti (Case Reports in Transplantation)
Graft-versus-host disease (GVHD) is a rare complication after solid organ transplantation and consists of a reaction of donor derived immune cells directed against host tissues. The vast majority of cases reported in the literature involve liver, small intestine and pancreas transplantation. We report a case of GVHD in a 48-year-old man after living-unrelated kidney transplantation at another center. Six months postoperatively he developed a skin rash, anorexia, and diarrhea that resulted in malnutrition and a 90 pound weight loss. At this point he was transferred to our center with a BMI of 16 and severe cachexia. Intravenous hyperalimentation was initiated and an extensive work-up for an infectious etiology was performed and was negative. An esophagogastroduodenoscopy was performed and revealed nodularity of the gastric mucosa, atrophy, and edema in the first and second portion of his duodenum. Biopsy findings were consistent with GVHD. Aggressive immunosuppressive therapy was instituted with a good response. The anorexia and diarrhea resolved, and he was discharged on hospital day 20. Three months later, there had been no recurrence of the diarrhea, the patient had gained an additional 40 pounds, BMI of 25, and a repeat upper endoscopy revealed complete resolution of the initial endoscopic abnormalities.